2020
DOI: 10.1002/solr.202000093
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Additives for Morphology Control in High‐Performance Lead‐Reduced Perovskite Solar Cells

Abstract: The organic–inorganic halide perovskite solar cells (PSCs) are rapidly developed in just a few years due to its high power conversion efficiency. However, it still faces some critical issues, one of which is the presence of toxic lead (Pb2+). Recent researches show that barium (Ba2+) can partially replace the Pb2+ in perovskite structure and achieve a promising device performance because of its adequate ionic radius. However, the optimal replacement amount of Ba2+ in perovskite is still limited. Herein, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 53 publications
1
33
0
Order By: Relevance
“…The average PCE of the PSC with MA 0.4 FA 0.6 Pb 0.9 Ba 0.1 I y Cl 3− y film is 15.0%. This efficiency performance is quite similar to our previous study [20b] . The lower fill factor (FF) may be attributed to the pinhole formation and incomplete surface coverage (Figure 2a).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The average PCE of the PSC with MA 0.4 FA 0.6 Pb 0.9 Ba 0.1 I y Cl 3− y film is 15.0%. This efficiency performance is quite similar to our previous study [20b] . The lower fill factor (FF) may be attributed to the pinhole formation and incomplete surface coverage (Figure 2a).…”
Section: Resultssupporting
confidence: 91%
“…The observation is consistent with our previous studies. [ 20 ] When x increased to 0.005, the pinholes on the surface of the perovskite film have significantly shrunk (Figure 2b). When the perovskite films were added the suitable amount of PEACl ( x = 0.01 and 0.03), some flake‐like and granular crystalline materials were formed between the perovskite grains (Figure 2c,d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al used the MA/FA mixed‐cation perovskite as the active layer in PSCs in which Pb 2+ was only partially substituted with Ba 2+ . [ 82 ] Using PEO as the polymer additive, the PSC fabricated using a 10.0 mol% Ba‐doped MA/FA mixed‐cation perovskite exhibited a PCE of 16.1% (Table 3: Report E). Cai et al systematically studied the influence of three essentially different polymers on the performance of planar PSCs fabricated based on an MAPbI 3 perovskite layer and low‐temperature‐processed TiO 2 .…”
Section: Properties and Classification Of Psc Polymeric Additivesmentioning
confidence: 99%
“…The power conversion efficiency (PCE) of organic–inorganic perovskite solar cells (PSCs) has been boosted to over 25% in the past decade, thus attracting tremendous attention. , Organic–inorganic perovskite possesses a lot of advantages as a light harvester, such as a high absorption coefficient in the visible region, adjustable composition and properties, ambipolar charge transport ability, and solution processability, which is compatible with low-cost, large-area, and roll-to-roll manufacture. On the other hand, the degradation of perovskite under moisture becomes one of the main drawbacks for commercial application, leading to insufficient long-term stability of PSCs. The water tolerance of perovskite can be moderately increased by composition engineering. For example, the incorporations of Br – , Cs + , and SCN – are demonstrated to show improved moisture stability of the mixed perovskite in a high-humidity environment. Hydroscopic polymer PEG is also employed in a perovskite film to bind MAI and prevent its escape in a humid atmosphere. , It is reported that 2D Ruddlesden-Popper perovskites containing diverse large alkylammonium cations exhibit higher hydrophobicity by inhibiting the ion migration . However, the stability of the perovskite often enhances at the expense of the enlargement of the band gap, which would impair the photovoltaic performance of the resultant devices .…”
Section: Introductionmentioning
confidence: 99%